In Silico Docking, Resistance Modulation and Biofilm Gene Expression in Multidrug-Resistant Acinetobacter baumannii via Cinnamic and Gallic Acids - Neveen A. Abdelaziz; Walid F. Elkhatib; Mahmoud M. Sherif; Mohammed A. S. Abourehab; Sara T. Al-Rashood; Wagdy M. Eldehna; Nada M. Mostafa; Nooran S. Elleboudy (MDPI AG, 2022)
Despite the mounting global burden of antimicrobial resistance (AMR), the generation of new classes of effective antimicrobials still lags far behind. The interplay between multidrug resistance and biofilm formation in Acinetobacter baumannii has drastically narrowed the available therapeutic choices. The use of natural compounds holds promise as an alternate option for restoring the activity of existing antibiotics and attenuating virulence traits through reduced biofilm formation. This study aimed to evaluate the modulatory effect of combining cinnamic and gallic acids at ½MIC with various antibiotics against multidrug-resistant (MDR) A. baumannii clinical isolates as well as study the effect on the expression of the biofilm-associated genes (bap, csuE, ompA) via quantitative, real-time PCR. Combining cinnamic or gallic acid with imipenem, amikacin or doxycycline resulted in significant reduction of resistance (p < 0.05). On the contrary, no effect was recorded when both acids were combined with levofloxacin, and only cinnamic acid had a synergistic effect with colistin. The transcriptomic changes of biofilm-related genes in the presence of gallic acid at ½MIC were compared with untreated control samples. The fold expression values proved that gallic acid substantially down-regulated the respective genes in all five strong biofilm formers. Molecular docking studies of gallic and cinnamic acids on target genes revealed good binding affinities and verified the proposed mechanism of action. To the best of our knowledge, this is the first report on the effect of gallic acid on the expression of bap, csuE and ompA genes in A. baumannii, which may permit its use as an adjunct anti-virulence therapeutic strategy.